Early study of dynamic assessment of phonological awareness in hearing impaired children - Ismail, Izzat (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
This early study was done to investigate the implementation of dynamic assessment to assess hearing impaired children performances. The other purpose of this study is to investigate the effects of teaching phonological awareness on the children listening skills. Through phonological awareness teaching also, the researcher investigates the learning ability of the children. This research was a case study done on 3 subjects; 1 cochlear implantee and 2 hearing aids wearer children. The subjects' age range is 8; 0 to 8; 6 years old. Cochlear implant subject hearing age was 6; 5 months old, the other two hearing aids wearers hearing age were 4; 6 years old and 5; 3 years old. The children had undergone pretest session to get the early information about the children achievement. Then, they had 2 mediated learning experience (MLE) sessions that teaches on how to perform in the test prepared by the researcher. After that, they had their post-test session. The data obtained were analyzed descriptively. The results reveal that dynamic assessment was proven to be successful in assessing hearing impaired children true potential. Post-test findings showed that listening skills improved for all of the children. Their learning ability of each child was discussed. Conclusion, dynamic assessment was proven effective for assessing children with hearing impaired true potential ruling out any possible biases. For clinical purpose, one can implement dynamic assessment in other communication disorders children.